Islamization and integration of sciences: the Kuantan Campus - Yunus, Kamaruzzaman; Hashi, Abdurezak Abdulahi; Ahmed Shogar, Ibrahim Adam (IIUM Press, 2019)
This chapter presents the process of Islamization and Integration of Sciences (IIS) in International Islamic University- Kuantan Campus (IIUM-KC) across the last few years. Islamization of Knowledge (IOK), as a process of actualizing principles of the Islamic worldview in educational system, is the soul of IIUM and its terminal goal. In this year, 2018, IIUM, Garden of Knowledge and Virtue, is celebrating its 35th anniversary of serving the mission of Islamization and integration of knowledge. From biological perspective, this is the age of physical and intellectual maturity for perfection of the task. It is no doubt that the educational philosophy and mission of IIUM is based on Islamization and integration of knowledge which inspired by (اقرأ), i.e. Recite, and guided by the Islamic principle of unity of knowledge. Aiming at instilling principles of the Islamic worldview on man, nature and God through educational process, IIUM is among the few universities in the world that undertaking this unique kind of mission. Seeking to serve the entire mankind, IIUM has been striving throughout the last three decades to reactivate the intellectual spirit of Islamic thought and the dynamic role of the Ummah among the other nations as imbued nation by knowledge and virtues. Focusing on creating an integrated academic environment, IIUM aims at a balanced growth of total personality of man, through holistic training of the spirit, intellect, and rationality. Instilling piety, development of self-discipline and self-purification are means of opening the heart to acknowledging God and proceeding to the realization of the status of mercy to all mankind. Focusing on Islamization process in IIUM-Kuantan Campos, this chapter presents the theoretical and practical steps that have been undertaken in actualizing the IIUM philosophy of education as prescribed above. It presents the Islamization and Integration of Sciences (IIS) in three basic parts. (i) The first part focuses on the theoretical matters of Islamization and integration of knowledge, such as the functional definition of IOK and its theoretical framework in IIUM-KC; (ii) The second part presents briefly the practical programmes and activities of Islamization and integration that have been undertaken by IIUM-KC, across the last few years; (iii) The third part includes the concluding remarks and guidelines for future direction.